2008
DOI: 10.1016/j.tet.2008.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-rich supramolecular metallacycles and metallacages

Abstract: Coordination-driven self-assembly via the directional-bonding approach utilizes rigid transition metal acceptors and electron-rich donors to allow for complex, nanoscale 2D polygons and 3D polyhedra to be prepared under mild conditions and in high yields. To ensure proper rigidity and directionality, many acceptor and donor precursors contain largely carbon-rich aromatic and/or acetylenic moieties. This article introduces self-assembly as an alternative means of synthesizing carbon-rich materials and discusses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 105 publications
0
27
0
Order By: Relevance
“…Substitution of the β positions of one of the pyridyl groups with chlorine atoms places these substituents too far from the Pt-N coordination site to effect self-organization. NMR spectroscopic analysis of a 1:1 mixture of 26 and 28 in CD 3 NO 2 indicated that isomer 29a was the most dominant species in solution. Isomers 29b and 29c were also formed as minor products while no evidence of isomer 29d could be observed.…”
Section: Non-absolute Self-organizationmentioning
confidence: 99%
“…Substitution of the β positions of one of the pyridyl groups with chlorine atoms places these substituents too far from the Pt-N coordination site to effect self-organization. NMR spectroscopic analysis of a 1:1 mixture of 26 and 28 in CD 3 NO 2 indicated that isomer 29a was the most dominant species in solution. Isomers 29b and 29c were also formed as minor products while no evidence of isomer 29d could be observed.…”
Section: Non-absolute Self-organizationmentioning
confidence: 99%
“… 1 , 2 The directional bonding approach is perhaps the most intuitive design strategy. 1g , 3 This approach entails the combination of donor (ligand) and acceptor (metal complex) units, the geometries of which determine the structure of the assembly formed. A fundamental requirement of this strategy is that these building blocks are shape-persistent; possessing conformational rigidity and well-defined coordinate vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The use of transition metal centres and coordination bonds has been proved to be an efficient method to obtain a great variety of discrete molecular architectures with different shapes and sizes that depends on the wide range of the species involved in the assembly process [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%